Genetic diversity of avian infectious bronchitis virus in commercial poultry flocks in select regions of the Philippines - Gagan, Gianne May R.; Zafra, Marie Sheryline L.; Atienza, Mark Lawrence G.; Arellano, Erika Joyce; Leynes, Leni Anjela D. C.; Tibayan, Yves Roy M.; Padaon, Dave Bryan R.; Ramoso, John Paolo A.; Rundina-Dela Cruz, Maria Cynthia N.; Camer, Gerry A.; Domingo, Ronnie D.; Endoh, Daiji; et al. (2022)
Avian infectious bronchitis (IB) is a highly contagious disease of domestic chickens caused by the avian infectious bronchitis virus (IBV). Albeit its known presence in the country, detailed information and field data are limited. To identify the predominant strains of IBV and characterize its clinical profile, a total of 37 field IBVs from selected regions in the Philippines were analyzed. Confirmed cases of IB were isolated from vaccinated flocks which presented mild to moderate respiratory, enteric, and nephropathogenic signs. Nucleotide sequencing and phylogenetic analysis of the partial S1 gene highlighted that all field IBVs belong to Genotype I. Sixteen (16) strains (43.24%) belong to GI-1 (Mass) lineage (H120-like = 11 strains (68.75%); Mass-like = five strains (31.25%)); one strain (2.70%) from GI-22 (CK/CH/LSC/99I-like) lineage; three strains (8.10%) from GI-25 (GA07) lineage; 11 strains (29.73%) were re-isolation of vaccine strains; and six (16.21%) strains were from an unknown lineage that might be distinct to the Philippines. Field IBVs were closely related (80-100%) to Chinese, US, Malaysian, and Thai IBV strains. This study demonstrated the co-circulation of multiple IBV lineages in the Philippines which may serve as an index for more targeted prevention and control strategies of IBV infection in the field.
Keywords: Poultry; Avian infectious bronchitis virus; PCR